Lexicons in Topeng Sidakarya Dance - I Wayan Wira Praditya; I Gede Budasi; Dewa Putu Ramendra (Universitas Negeri Makassar, 2023)
Abstract. Topeng Sidakarya dance was one of the classics that originated in the 16th century that related to the story of the arrival of Brahmana Keling in Bali. The dance had many lexicons in the Balinese language. This study aims at investigating the lexicons in the Topeng Sidakarya dance and their cultural meanings. This study was conducted as descriptive qualitative research using an ethnolinguistic approach. The method of data collection are observation and interviews. The research instruments include the researcher as the main instrument, an observation sheet, an interview guide, and a phone recorder. The result of this study shows that sixteen (19) lexicons were related to movements (three in head movements, ten in body movements, and three in leg movements). The cultural meanings of the lexicons are related to the Balinese Hindu leadership concepts, namely Panca Upaya Sandhi, Nawanatya, Tri Upaya Sandhi, Sad Warnaning Raja Niti, Panca Dasa Pramiteng Prabhu. In addition, the dance movements also illustrate the Tri Hita Karana concept (harmony with God, people, and nature). This study is beneficial for language teaching and dance teachers, where the result of the lexicons found can be used to teach the Balinese language and dance; therefore, it can maintain the existence of Balinese language and culture from extinction. Keywords: Topeng Sidakarya, lexicons, cultural meaning, ethnolinguistic